Mood and anxiety problems in perinatal Indigenous women in Australia, New Zealand, Canada, and the United States: A critical review of the literature. (February 2014) - Bowen, Angela; Duncan, Vicky; Peacock, Shelley; Bowen, Rudy; Schwartz, Laura; Campbell, Diane; Muhajarine, Nazeem
We conducted a review of research literature related to anxiety, depression, and mood problems in Indigenous women in Canada, the United States (including Hawaii), Australia, and New Zealand. Quantitative and qualitative research studies published between 1980 and March 2010 were reviewed. The initial search revealed 396 potential documents, and after being checked for relevance by two researchers, data were extracted from 16 quantitative studies, one qualitative research article, and one dissertation. Depression is a common problem in Indigenous pregnant and postpartum women; however, the prevalence and correlates of anxiety and mood disorders are understudied. The review identified four key areas where further research is needed: (a) longitudinal, population-based studies; (b) further validation and modification of appropriate screening tools; (c) exploration of cultural diversity and meaning of the lived experiences of antenatal and postpartum depression, anxiety, and mood disorders; and (d) development of evidence-informed practices for researchers and practitioners through collaborations with Aboriginal communities to better understand and improve mental health of women of childbearing age.